Pola Stratifikasi Massa Air Di Perairan Teluk Ambon Pada Bulan Mei, Juni, Dan Juli 2024 - Pelu, Fadli (CV. SINAR HOWUHOWU, 2025)
Ambon Bay is a semi-enclosed coastal system characterized by complex oceanographic dynamics influenced by seasonal variability, tidal processes, and freshwater input from surrounding land areas. This study aims to analyze the vertical stratification patterns of temperature, salinity, and density, as well as the water mass movement in Ambon Bay Inner (ABI) and Ambon Bay Outer (ABO) during May, June, and July. Observations were conducted at several stations representing a transverse section of the bay, and the data were analyzed based on the vertical distribution of physical parameters and seawater density (Sigma-T). The results indicate that temperature, salinity, and density exhibit significant vertical and temporal variations, with the highest values generally occurring in May. Vertically, temperature and salinity tend to be lower in the surface layer and increase with depth, resulting in a corresponding increase in seawater density. The water mass movement pattern shows that circulation in Ambon Bay is largely controlled by tidal forcing, with water masses forming distinct layers of varying thickness at different depths. Density stratification plays a crucial role in regulating vertical mixing processes and controlling water mass dynamics within the bay. These findings provide important insights into the physical characteristics of Ambon Bay and can support sustainable coastal and marine resource management.